(untitled) (Contemporary Journal of Social Science Review, 2025)
Substance use disorders represent a major public health concern in South Asia, yet the lack of culturally and linguistically validated diagnostic instruments limits accurate assessment and research. Standardized tools grounded in DSM-5 criteria are essential for reliable screening and severity evaluation in Urdu-speaking populations. The primary objective of this study was to translate and psychometrically validate the DSM-5 Checklist for Substance Use Disorders in the Urdu language. The present study was conducted in two phases. Phase I involved the translation of the scale using Brislin guidelines, while Phase II focused on validating the translated version. A cross-sectional research design and purposive sampling technique were used to recruit a sample of 300 participants. Confirmatory Factor Analysis (CFA) was performed to validate the factor structure of the Urdu version. Psychometric properties were evaluated using Cronbach’s alpha reliability and assessments of correlation with other variables. The scale demonstrated excellent reliability and validity, with a Cronbach’s alpha of 0.93. Confirmatory factor analysis indicated an excellent fit, with all goodness-of-fit indices exceeding recommended thresholds and RMSEA within acceptable limits, supporting the factorial validity of the Urdu DSM-5 Checklist for Substance Use Disorders. The Urdu DSM-5 Checklist for Substance Use Disorders demonstrated strong positive correlations with the DAST-10, supporting convergent validity, and weak negative correlations with the Rosenberg Self-Esteem Scale, confirming discriminant validity. These findings indicate that the Urdu-translated checklist is a reliable and valid instrument, facilitating culturally appropriate research, diagnostic screening, and assessment of symptom severity among Urdu-speaking populations.